Starch and protein hydrolysis in cooked quinoa (Chenopodium quinoa Willd.) during static and dynamic in vitro oral and gastric digestion. Issue 2 (10th January 2022) - Tagle-Freire, Danny; Mennah-Govela, Yamile; Bornhorst, Gail M.
Abstract : Differences in particle size and type of digestion model impacted pH, and protein and starch hydrolysis during gastric digestion of quinoa. Abstract : Quinoa is a pseudocereal that has a favorable nutrient profile and may be a beneficial addition to the diet. To evaluate potential health-promoting properties of foods, it is important to understand the rate of macronutrient hydrolysis, which is commonly quantified through in vitro digestion studies. Additionally, limited information is available comparing starch and protein hydrolysis of solid foods using static and dynamic digestion models. The objective of this study was to examine starch and protein hydrolysis in cooked quinoa using a combination of a static (saliva only) or dynamic (saliva + mincing) oral digestion model with a static (gastric fluids only) or dynamic (Human Gastric Simulator) gastric digestion model. Disruption of the pericarp of the cooked quinoa seeds during dynamic oral digestion released additional surface area, which led to faster gastric emptying during dynamic gastric digestion. Starch and protein hydrolysis were impacted by type of gastric model due to differences in pH and variations in structural breakdown. Starch hydrolysis was 29.04 ± 1.83% after 180 min dynamic gastric digestion compared to 2.85 ± 1.88% during static gastric digestion (averaged across both oral digestion models). The degree of protein hydrolysis was 4.85 ± 0.01% after 180 min in the static gastric model compared to 3.94 ± 0.18% in the dynamic gastric model (averaged across both oral digestion models). This information provides evidence on the role of food structure and breakdown (through use of static vs. dynamic oral and gastric digestion models) on quinoa starch and protein hydrolysis.